Animal model of simulated microgravity: a comparative study of hindlimb unloading via tail versus pelvic suspension. Issue 1 (12th June 2013) - Chowdhury, Parimal; Long, Ashley; Harris, Gabrielle; Soulsby, Michael E.; Dobretsov, Maxim
Abstract: The aim of this study was to compare physiological effects of hindlimb suspension (HLS) in tail‐ and pelvic‐HLS rat models to determine if severe stretch in the tail‐HLS rats lumbosacral skeleton may contribute to the changes traditionally attributed to simulated microgravity and musculoskeletal disuse in the tail‐HLS model. Adult male Sprague‐Dawley rats divided into suspended and control‐nonsuspended groups were subjected to two separate methods of suspension and maintained with regular food and water for 2 weeks. Body weights, food and water consumption, soleus muscle weight, tibial bone mineral density, random plasma insulin, and hindlimb pain on pressure threshold (PPT) were measured. X‐ray analysis demonstrated severe lordosis in tail‐ but not pelvic‐HLS animals. However, growth retardation, food consumption, and soleus muscle weight and tibial bone density (decreased relative to control) did not differ between two HLS models. Furthermore, HLS rats developed similar levels of insulinopenia and mechanical hyperalgesia (decreased PPT) in both tail‐ and pelvic‐HLS groups. In the rat‐to‐rat comparisons, the growth retardation and the decreased PPT observed in HLS‐rats was most associated with insulinopenia. In conclusion, these data suggest that HLS results in mild prediabetic state with some signs of pressure hyperalgesia, but lumbosacral skeleton stretch plays little role, if any, in these pathological changes. Abstract : e00012 Abstract : The aim of this study was to compare physiological effects of hindlimb suspension (HLS) in tail‐ and pelvic‐HLS rat models to determine if severe stretch in the tail‐HLS rats lumbosacral skeleton may contribute to the changes traditionally attributed to simulated microgravity and musculoskeletal disuse in the tail‐HLS model. The results of the study suggest that HLS results in mild prediabetic state with some signs of peripheral nerve disease, but lumbosacral skeleton stretch plays little role, if any, in these pathological changes.